2020
DOI: 10.1108/ijrdm-12-2019-0399
|View full text |Cite
|
Sign up to set email alerts
|

Exploring young consumer's decision‐making for luxury co-branding combinations

Abstract: PurposeThe purpose of this paper is to identify the realistic trade-offs young consumers make when evaluating luxury co-branding combinations based on signalling theory.Design/methodology/approachConjoint analysis was employed to evaluate the relative impact of four major attributes (i.e. brand combinations, retail channels, uniqueness and price) on consumer desirability for luxury co-branding combinations. The data were analysed using desirability indices.FindingsBrand combinations, uniqueness and price signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 71 publications
0
11
0
2
Order By: Relevance
“…In the case of the literature on co‐branding success factors, there is an insufficient number of papers on some of the variables such as variety seeking (Mazodier & Merunka, 2014), brand involvement (Moon & Sprott, 2016), dialectical self (Wang et al, 2020), retail channel (e.g. Yu et al, 2020) and sensory fit (e.g. Ahn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of the literature on co‐branding success factors, there is an insufficient number of papers on some of the variables such as variety seeking (Mazodier & Merunka, 2014), brand involvement (Moon & Sprott, 2016), dialectical self (Wang et al, 2020), retail channel (e.g. Yu et al, 2020) and sensory fit (e.g. Ahn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Existing brand literature conceptualises the consumer‐based brand equity as a composite of many consumer perception aspects, such as brand association, brand image, perceived quality, brand familiarity and brand awareness (Aaker, 1991; Keller, 1993), and also incorporates consumer behaviour aspects, such as preferences, loyalty, and purchase intention (Aaker, 1991; Agarwal and Rao, 1996). The researchers in co‐branding literature have extensively investigated the impact of one or more aspect of brand equity of partnering brands on co‐branding evaluation (Ma et al, 2018; Yu et al, 2020).…”
Section: Overview Of the Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining two well-known brands can be a signal for consumers to represent the image of the product being offered (Washburn et al, 2000). Previous research found that to identify the realistic trade-offs that young consumers make when evaluating luxury co-brand combinations based on signal theory (Yu et al, 2020). Furthermore, the historical relationship of the prospective brand is another important thing to consider (Nasution et al, 2020), where the success of communication reach is embedded through a motivational touch, which is given to the final consumers creating a sense of integrity (Raja, 2020).…”
Section: Introductionmentioning
confidence: 99%